Relasi Tasawuf dengan Pendidikan Karakter - Dedi Junaedi; Norcahyono Norcahyono (Al-Liqo: Jurnal Pendidikan Islam, 2020)
Sufism means reviving the relationship between man and Allah SWT. Awareness of the sense of connection with Allah SWT will place a person to pleasure and mahabbah and ma'rifat, then he will not be disturbed by the changes of time during his life because the center of attention is no longer on those who change, but on those who remain unchanged, that is Allah SWT. Humans in this life need education as a means of communication with those in need. So, in this case, religious education is a very fundamental foundation in achieving the goals both ethically and aesthetically. Takhalli is a way of purifying oneself from reprehensible traits, such as jealousy or envy, suudzan, kibir, ujub, ria, suma ', bakhul, hubbul mal, tafahur, ghadab, ghibah, namimah, kizib, treachery. Then Tahalli by filling himself with praiseworthy attributes such as repentance, khauf, sincerity, gratitude, asceticism, patience, ridha, tawakal, mahabbah, zikrul maut, and getting closer to Allah SWT with four levels of perfection of Islam among them is the first Shari'ah, the second tariqat, the third fact, the fourth ma'rifat. This study discussed what is Sufism and education, how is the relationship between Sufism and education.